Effectiveness of hand exercise on limb function in patients coronary artery disease post trans-radial artery catheterization: systematic review - Herdiana, Dian Herdiana; Herawati, Tuti; Yona, Sri (Universitas Muhammadiyah Semarang, 2024)
Coronary Artery Disease (CAD) is the leading cause of mortality worldwide. Catheterization using the transradial arterial (TRA) technique has been able to reduce morbidity and mortality rates from CAD, but this procedure also contributes to the occurrence of complications. This study aims to search the literature and analyse articles discussing the use of hand exercise to improve limb function in patients after trans-radial cardiac catheterization. The design used was a systematic review with PRISMA adaptation. Articles were searched using databases: ScienceDirect, Proquest, PubMed, Scopus and Hand Searching in Google Scholar. The results are discussing 7 articles published from 2013-2023. Hand exercises are useful for restoring limb function within two hours after the procedure and over a long period. To deliver nursing interventions that reduce pain, oedema, and bleeding in CHD patients undergoing trans-radial cardiac catheterization, it is established that hand exercise can develop into an evidence-based reference. Long-term hand exercise training can also enhance endothelial function, which controls blood vessel vasoconstriction and dilatation. This enhances circulation during activity, improves grip function, and enhances extremities function.